2022
DOI: 10.1177/00220221221109547
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Self-Compassion and Life Satisfaction Varies Across Societal Individualism-Collectivism: A Three-Level Meta-Analysis

Abstract: Self-compassion is positively correlated with life satisfaction. However, no previous work examined the cross-cultural difference regarding the effect size of this correlation. Using 79 independent samples ( N = 23,976) from 26 countries/regions, this three-level meta-analysis synthesized the effect sizes of their correlation, partitioned the between-study heterogeneity into the within- and between-country levels, and examined the moderating role of national culture according to the revised Minkov-Hofstede mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 136 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Intrinsic motivation and self-compassion were associated with each other in many other samples, but not in the Indonesian student sample. We suggest this may be due to collectivistic experience of self-compassion as opposed to individualistic experience of self-compassion, focusing on the self [ 66 ]. Future research is needed to understand which component of self-compassion is related the most to each type of motivation among Indonesian students.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic motivation and self-compassion were associated with each other in many other samples, but not in the Indonesian student sample. We suggest this may be due to collectivistic experience of self-compassion as opposed to individualistic experience of self-compassion, focusing on the self [ 66 ]. Future research is needed to understand which component of self-compassion is related the most to each type of motivation among Indonesian students.…”
Section: Discussionmentioning
confidence: 99%
“…Following the prevalent practice in research examining cultural context, we used publicly available data on country level indicators of cultural tightness (for examples, see Luo et al, 2023;Shi et al, 2024; and collectivismindividualism (for examples, see Germani et al, 2021;Huppert et al, 2019;Lu et al, 2021;Wang & Lou, 2022). The tightness-looseness country-level scores were taken from taken from Eriksson et al, 2021, and the collectivism-individualism country-level scores were taken from .…”
Section: Tightness-looseness and Collectivism-individualismmentioning
confidence: 99%
“…Being sympathetic toward others does not automatically translate into being compassionate about oneself. Wang and Lou (2022) revealed that selfcompassion and life happiness were positively correlated in various cultural civilizations after conducting a cross-cultural study with 23,976 people from 26 countries.…”
Section: Introductionmentioning
confidence: 99%